2015
DOI: 10.5152/tud.2015.03442
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ureterolithotomy; which is better: Transperitoneal or retroperitoneal approach?

Abstract: Objective: This was a prospective study to compare the outcome of laparoscopic transperitoneal ureterolithotomy (LTU) with laparoscopic retroperitoneal ureterolithotomy (LRU) as a primary treatment for a large stone in the proximal ureter. Material and methods:A total of 24 patients with a solitary, large (>1.5 cm), and impacted stone in the proximal ureter was selected and randomly divided into two groups. The first group included 13 patients who were treated by LTU, and the second group included 11 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…Keeley et al reviewed their experience with TPLU in 14 patients; in their study, low grade fever was detected in one patient(26). In the study by Khalil and coworkers, postoperative fever was observed in 15.4% of the TPLU group(27). In our study, low grade fever was present in 8 (13.3%) patients which relieved by administration of a suitable antipyretic drug.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…Keeley et al reviewed their experience with TPLU in 14 patients; in their study, low grade fever was detected in one patient(26). In the study by Khalil and coworkers, postoperative fever was observed in 15.4% of the TPLU group(27). In our study, low grade fever was present in 8 (13.3%) patients which relieved by administration of a suitable antipyretic drug.…”
supporting
confidence: 48%
“…Blood transfusion was needed to restore the hemodynamic state in 8 (13.3%) patients. In the study by Khalil and coworkers, the need for blood transfusion in the TPLU group was 15.4%(27). Chen et al, comparing safety and efficacy between TPLU and RLU for proximal ureteral stones > 10 mm, mentioned that the overall rate of blood transfusion was 2.8%(12).…”
mentioning
confidence: 99%
“…LUL with both trans-peritoneal and retroperitoneal techniques have been used for large impacted ureteric calculi, with stone size more than 15 mm, and it has been found that both approaches are effective. The trans-peritoneal technique has significantly shorter operative time and lower rate of open conversion but has a significantly longer time to oral intake [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…LUL with both transperitoneal and retroperitoneal techniques have been used for large impacted ureteric calculi, with stone size more than 15 mm and it has been found that both approaches are effective. The transperitoneal technique has signi cantly shorter operative time and lower rate of open conversion but has a signi cantly longer time to oral intake [3].…”
Section: Discussionmentioning
confidence: 99%